Prevalence of depressive symptoms among elderly and its predictors: a cross sectional study in community felda Bukit Goh, Kuantan Pahang - Md Aris, Mohd Aznan; Che' Man, Mohamad; Sulaiman, Nur Suriati; Yusof, Muhammad Zubir (Science Forecast Publications, 2019)
Introduction: The world’s population is ageing rapidly. Older people are at risk of having mental illnesses particularly depression but it is often misdiagnosed and undertreated. It affects general wellbeing and daily functions of the patients. Objectives: To measure the prevalence of depression and its associated factors among elderly living in FELDA Bukit Goh, Kuantan, Pahang. Methodology: A cross sectional study was conducted from June to September 2018. The participants aged more than 60 years were recruited in this study. A total of 259 participants were randomly selected to complete the interviewed-base questionnaire. The questionnaire consisted of four sections which included the sociodemographic, Geriatric Depression Scale (GDS), Elderly Cognitive Assessment Questionnaire (ECAQ) and Modified Barthel Index (MBI). Descriptive statistics was used to measure the prevalence and logistic regression to explore the association of depression with the background variables. Results: Out of 259, the majority were female. It was found that 19.3% of them were having depression. The associated factors were elderly without formal education (adjusted Odds Ratio (aOR):2.38, 95% Confidence Interval (CI):1.07-5.31), cognitive impairment (aOR: 3.68, 95% CI 1.29-10.5), and marked dependence (aOR: 3.17, 95% CI: 1.47-6.86). Conclusions: The prevalence of depression among elderly was considerably alarming. Health personnel whose managing elderly patients should take initiative at any given chances to screen for depression especially among those without formal education, cognitive impairment and marked dependent in their activities of daily living.